Estimasi Kebutuhan Material Cat Pada Bottom dan Lambung Kapal Tongkang 300 Feet - Diana L. Mustikawati; Iman Mujiarto (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2023)
Improvements in terms of protection against corrosion are carried out regularly in the shipping industry. One alternative that is used is painting or coating. Painting is a method to prevent the plate from corroding. Coating is a stage that must be passed in the ship repair and construction process. In the ship repair process, material needs are importhant things that must be planned. The paint or coating material used in this study is paint according to specifications for the shipping industry. The purpose of this study was to obtain the required cat consumption based on surface area reference. The ship repair and construction process includes coating or painting work. The need for paint is based on the surface area of the underwater, bottom and topside of the 300 feet barge that will be painted. This research is a quantitative research where the final result is in the form of numbers. Results of calculating the area of ​​the ship: a. Flat bottom painting of 1926.06 m2; b. Painting the lower vertical area of ​​22.32 m2; c. Painting the lower area of ​​717.82 m2 and d. Painting of the topside area of ​​296.5 m2. The calculation of the cat's needs is that the underground (flat and vertical bottom) is 1717.96 liters and the bottomtop and topside are 738.24 liters. The research conclusions obtained were that the smallest volume of cat used in underwater painting was 1717.96 liters and in the bottom - topside area was 738.24 liters and the surface area under water (flat bottom and vertical bottom) was 2150.38 m2 ( 2150 m2) and the bottom-topside area is 1014.32 m2 ( 1014 m2).